2021
DOI: 10.1007/s11356-021-15161-1
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between urbanization and water environment based on coupling analysis in Nanjing, East China

Abstract: The degradation of water environment (WE) has constrained the sustainable development of cities, while the rapid urbanization also exacerbates water environment change. However, the complicated relationship between urbanization and WE is far from clearly understood. In this study, a comprehensive index system for urbanization and WE was applied along with the System Index Evaluation Model (SIEM) and a Coupling Coordination Degree Model (CCDM) to analyze the coupling between urbanization and WE in Nanjing, East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 81 publications
1
18
1
Order By: Relevance
“…Economic development and expanding land use activities are directly linked to an increase in waste production. Similar observations were reported by [1][2][3][4]. According to Camara et al [6], the higher percentages of land use associated with human activities and economic development in watersheds are often interrelated with high concentrations of water pollutants, while undeveloped areas such as natural forest areas are linked with good water quality.…”
Section: Introductionsupporting
confidence: 76%
“…Economic development and expanding land use activities are directly linked to an increase in waste production. Similar observations were reported by [1][2][3][4]. According to Camara et al [6], the higher percentages of land use associated with human activities and economic development in watersheds are often interrelated with high concentrations of water pollutants, while undeveloped areas such as natural forest areas are linked with good water quality.…”
Section: Introductionsupporting
confidence: 76%
“…Shi [ 22 ], Zhao et al [ 23 ], Xie et al [ 24 ], Yao et al [ 25 ] and Wang et al [ 26 ] used comprehensive indicator evaluation model, random effect panel Tobit model, improved STIRPAT model, coupling coordination degree model and other research methods to empirically analyze the spatial-temporal pattern and influencing factors of the coupling coordination between new-type urbanization and ecological environment. Yang et al [ 27 ], Liu et al [ 28 ], Shi [ 29 ], Liu and Zhi [ 30 ], Han et al [ 31 ], Cui et al [ 32 ], Shang and Jiang [ 33 ], Feng et al [ 34 ], Zhu et al [ 35 ], Yang et al [ 36 ], Ma et al [ 37 ] take, respectively, Shaanxi Province, Fujian Province, China’s coastal zone, Beijing city, the Yangtze River economic belt, the Yellow River Basin, the Tibet Autonomous Region, the pan third pole region, the Wanjiang demonstration area, Cheng-Yu urban agglomeration and Nanjing city as case-study examples to calculate, analyze and evaluate the coupling coordination degree of urbanization and ecological environment through the construction of indicator system of urbanization and ecological environment evaluation. These studies revealed that due to regional differences, different selection of evaluation indicators, different local policies and economic development and other factors, the urbanization process, ecological environment and the coupling coordination between the two in each regions exhibit different characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…To fill this gap in the literature, this paper will build the evaluation indicator system of new-type urbanization and water ecological environment in Jiangxi Province, and use the entropy method, coupling coordination degree model and random effect panel Tobit model to study the coupling coordination development status between new-type urbanization and water ecological environment, and also its driving factors in Jiangxi Province and its 11 cities, in order to explore a mutually beneficial win-win road to promote the coordinated development of new-type urbanization and water ecological environment in Jiangxi Province. Compared with the research of Zhu et al [ 35 ], Yang et al [ 36 ], and Ma et al [ 37 ], we further use the linear weighting method to measure the comprehensive score of new-type urbanization and water ecological environment system in Jiangxi Province based on the entropy method. We also build a new coupling coordination degree model which can fully and truly reflect the coordinated development degree between the two subsystems of new-type urbanization and water ecological environment.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the decoupling relationship of demographic urbanization from carbon emissions and spatial urbanization from carbon emissions are similar, and the decoupling relationship of economic urbanization from carbon emission and social urbanization from carbon emission are also similar. This shows that demographic urbanization and spatial urbanization have similar trends, while economic urbanization and social urbanization show similar patterns, which is similar to the development of Nanjing, China (Ma et al, 2021). However, the decoupling statuses of urbanization from carbon emissions in different African countries is obviously J o u r n a l P r e -p r o o f 22 different.…”
Section: Similarities and Differences Of Decoupling Statusesmentioning
confidence: 68%